IDENTIFIKASI KANDUNGAN METABOLIT SEKUNDER DAUN AKAR WANGI (Vetiveria zizanioides (L). Nash) DAN POTENSINYA SEBAGAI INSEKTISIDA NABATI - Purwati, Sri; Jailani, Jailani; Masitah, Masitah (Partner, 2024)
ABSTRAKPestisida nabati adalah salah satu alternatif untuk mengendalikan serangan hama. Salah satunya adalah akar wangi. Identifikasi senyawa metabolit sekunder perlu diketahui karena merupakan sumber penting untuk memperoleh data pestisida nabati dan produk turunan pestisida nabati. Tujuan penelitian ini adalah untuk mengetahui kandungan metabolit sekunder dari ekstrak etanol daun akar wangi (Vetiveria zizanioides (L.) Nash) dan potensinya sebagai pestisida nabati. Penelitian ini melakukan uji fitokimia secara kualitatif terhadap kandungan esktrak etanol daun akar wangi. Hasil penelitian menunjukkan bahwa ekstrak etanol dari daun akar wangi mengandung flavonoid, tanin, fenolik, dan alkaloid. Selain itu, tidak ditemukan steroid atau saponin dalam ekstrak. Telah ditentukan bahwa ekstrak etanol daun akar wangi mengandung metabolit sekunder seperti flavonoid, tanin, fenolik, dan alkaloid, yang mana kandungan metabolit sekunder daun akar wangi ini berpotensi untuk digunakan sebagai pestisida nabati guna mengurangi jumlah hama yang menyerang tanaman. Kata kunci: daun akar wangi, metabolik sekunder, pestisida nabati   ABSTRACTPlant-based pesticides are one of the alternatives to control pest attacks. One of them is vetiver. The identification of secondary metabolite compounds needs to be known because it is an important source of obtaining data on vegetable pesticides and vegetable pesticide derivatives. The purpose of this study was to determine the secondary metabolite content of ethanol extract of vetiver leaves (Vetiveria zizanioides (L.) Nash) and its potential as a botanical pesticide. This study conducted qualitative phytochemical tests on the content of ethanol extract of vetiver leaves. The results showed that ethanol extract of vetiver leaves contained flavonoids, tannins, phenolics, and alkaloids. In addition, no steroids or saponins were found in the extract. It has been determined that the ethanol extract of vetiver leaves contains secondary metabolites such as flavonoids, tannins, phenolics, and alkaloids, which contain secondary metabolites of vetiver leaves, which have the potential to be used as vegetable pesticides to reduce the number of pests that attack plant. Keywords: vetiver leaves, secondary metabolism, botanical pesticides